The potential role of artificial intelligence to promote the participation and inclusion in physical exercise and sports for people with disabilities: A narrative review - Rosa, João Paulo Pereira [UNESP] (Elsevier, 2025)
The lack of physical activity presents a significant public health concern, particularly for individuals with disabilities who face heightened risks due to sedentary lifestyles. Despite progress, personal and environmental obstacles persist, hindering accessibility and full engagement in physical activities for people with disabilities, particularly children and adolescents. This narrative review highlighted the Artificial Intelligence (AI), in which emerges as a promising tool to address these challenges. By leveraging AI-powered assistive technologies, individuals with disabilities can overcome barriers, augment independence, and improve their overall quality of life. AI facilitates alternative communication avenues, enhances accessibility, and offers personalized exercise programs tailored to individual needs. Monitoring training metrics using AI systems provides valuable insights and feedback, promoting active participation and progress tracking. The dynamic relationship between AI and disability support continues to evolve, offering future opportunities for increased inclusivity and accessibility in sports and exercise environments.
Keywords: Adapted sports; Artificial intelligence; Assistive technologies; Disabled persons